Principal – Agent theory approach for determination of appropriate ‘Activity Model’ for cadastral information updating in Nepal - Paudyal, Dev Raj (Journal on Geoinformatics, Nepal, 2006)
In Nepal due to the increased need of agricultural based economical activities and rural to urban transactions process there is a need of reliable and ready access to cadastral information. The Ministry of Land Reform and Management (MoLRM) has targeted to develop nationwide LIS for updating and dissemination of reliable and accurate land information. A LIS consists of two databases an administrative/legal system i.e. attribute data and a digital cadastral map i.e. spatial data containing the ownership, value and use of land. The Department of Land Information and Archive (DoLIA) has started developing district wise LIS. This approach needs much more resources in comparison to the centralized LIS. From financial perspective the updating of cadastral information is much more expensive than the land registry information. So, there is a need of determination of appropriate ‘‘Activity Model’’ for cadastral information updating process. This research paper provides an approach for determination of appropriate ‘Activity Model’ for cadastral information updating in Nepal. The Principal - Agent (PA) theory approach has been used for the determination of appropriate ‘Activity Model’. Six different options according to the P-A relationships were evaluated with twenty institutional and technical parameters and found that CC (central authority and central activity) is optimal for cadastral information updating procedure. Eight different processes for the cadastral information updating are identified and modeled them using object oriented modeling techniques with UML activity diagram. Two ways of verification has been used to test the model. The model is conceptually tested developing use cases with the help of activity diagram. The feasibility of the model is tested using Arc cadastre software with the direct link to geodatabase.